2015
DOI: 10.4049/jimmunol.1402147
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1–Triggered Release of Type I IFN by Plasmacytoid Dendritic Cells Induces BAFF Production in Monocytes

Abstract: HIV-1 infection leads to numerous B cell abnormalities, including hypergammaglobulinemia, nonspecific B cell activation, nonspecific class switching, increased cell turnover, breakage of tolerance, increased immature/transitional B cells, B cell malignancies, as well as a loss of capacity to generate and maintain memory, all of which contribute to a global impairment of the immune humoral compartment. Several cytokines and soluble factors, which are increased in sera of HIV-1–infected individuals, have been su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 71 publications
0
35
0
Order By: Relevance
“…Moreover, we reported that HIV-1-directed release of type-I IFN by pDCs plays a determinant role in BAFF production by monocytes (30). As shown in Fig.…”
Section: Hiv-1-mediated Baff Production In Mdms Is Independent Of Typmentioning
confidence: 82%
See 4 more Smart Citations
“…Moreover, we reported that HIV-1-directed release of type-I IFN by pDCs plays a determinant role in BAFF production by monocytes (30). As shown in Fig.…”
Section: Hiv-1-mediated Baff Production In Mdms Is Independent Of Typmentioning
confidence: 82%
“…We previously reported that the release of type-I IFN by pDCs following exposure to HIV-1 drives BAFF expression in human monocytes (30). These results motivated us to investigate whether HIV-1 could also modulate BAFF production in macrophages, because they represent another important cellular source of BAFF (35,36,(44)(45)(46)(47) and are, contrary to monocytes, permissive to productive HIV-1 infection (48).…”
Section: Hiv-1 Increases Baff Expression and Secretion In Mdmsmentioning
confidence: 99%
See 3 more Smart Citations